Development of a CE‐MS method for the study of riociguat and metabolite M1 in pharmaceutical analysis - Štícha, Martin; Hložek, Tomáš; Bursová, Miroslava; Čabala, Radomír; Jelínek, Ivan (Electrophoresis, 2019)
Riociguat is a novel antihypertensive drug for the treatment of pulmonary hypertension. We present electrophoretic characterization, i.e. migration behavior of riociguat and metabolite M1 as support for optimized CZE/MS assay. Fundamental separation parameters, such as peak width, symmetry, and resolution are studied in a series of ammonium formate buffers within pH range 2.60–5.61. The narrow region of peak symmetry lies close to pH 4.0 for both analytes. Accordingly, the value of resolution maximizes in a background electrolyte adjusted to pH 4.10. Basic calibration parameters estimated from CZE experiments with absorption photometric and mass spectrometric detection of riociguat and metabolite M1 were evaluated. More than three orders lower LOD was achieved with high resolution mass spectrometric detection. The observed difference in the sensitivity of both detection techniques gives priority to the utilization of CZE/MS in practice. The values of dissociation constants of riociguat and metabolite M1, pKBH, were determined from CZE measurements in lithium formate and lithium acetate background electrolytes with constant ionic strength. The value of pKBH = 4.30 ± 0.02 for riociguat corresponds well to the value already presented in the literature. According to our observation, metabolite M1 behaves like a slightly stronger base with estimated pKBH = 4.40 ± 0.02.